Literature as a source of perplexity The contribution of the story in the problem of the self, in the concept of Refiguration by Paul Ricoeur. (2005)
The affirmation that in the encounter with the works of art a knowledge about himself is elaborated, is approached from the concept of the refiguration of Paul Ricoeur. It is intended to investigate the way in which, as a reader, knowledge about himself i